Implementasi Model AISAS dalam Penulisan Naskah Reels pada Instagram @pln.iconplus - Siti Ainun Arsy; Alfa Taufan Latif; Fikry Fachrurrizal (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
Fierce competition in digital marketing demands creativity in short-form video content. This study aims to analyze the implementation of the AISAS (Attention, Interest, Search, Action, Share) model in writing Instagram Reels scripts for the @pln.iconplus account, using a sample video titled "GRWP! Ayo Ayo Ayo." This study employs a descriptive qualitative approach through theoretical script analysis using the Stimulus-Organism-Response (S-O-R) framework, supported by secondary data from Instagram Insights engagement metrics. The results indicate that PLN Icon Plus successfully converted rigid corporate bureaucratic messages into a tactical and dynamic narrative. In the Attention and Interest phases, the use of Medium Shot techniques and jump cut pacing every 1.5–2 seconds effectively triggered a pattern interrupt to maintain viewer retention. Meanwhile, in the Action and Share phases, humorous elements from popular culture successfully triggered emotional responses that drove organic interactions. The success of this strategy is empirically proven by Instagram Insights data, which recorded 11,600 views, 6,432 reach, 347 likes, 11 comments, 7 saves, and 28 shares, yielding a definitive Engagement Rate (ER) of 6.11%, significantly outperforming the industry average of 1%–3%. The study concludes that integrating the AISAS formula, complying with SOPs, and adapting digital culture in scriptwriting can significantly enhance corporate brand communication effectiveness on social media.